Digitization of Endocytic pH by Hybrid Ultra‐pH‐Sensitive Nanoprobes at Single‐Organelle Resolution. Issue 1 (4th November 2016) - Wang, Yiguang; Wang, Chensu; Li, Yang; Huang, Gang; Zhao, Tian; Ma, Xinpeng; Wang, Zhaohui; Sumer, Baran D.; White, Michael A.; Gao, Jinming
Abstract : A multispectral hybrid nanotransistor consisting of modular fluorescent block copolymers with discrete and sharp pH transitions in one nanoparticluate system is presented. This nanotransistor probe allows digitized reporting of dynamic maturation at single‐organelle resolution over time. This nanotechnology platform offers a powerful tool in fundamental studies of organelle biology, cell signaling in diseases characterized by pH dysregulation in the endosomes or lysosomes.